GLOBAL LOGISTICS AND SUPPLY CHAIN MANAGEMENT - Mangan, John; Lalwanis, Chandra; Calatayud, Agustina (Wiley, 2021)
"This chapter lays the foundations of the textbook and explains the origins and applications of logistics and supply chain management, as well as giving descriptions of key concepts. A framework for the textbook is developed and this illustrates where each chapter fits in the overall schema of the book, while the various perspectives adopted by the authors when writing this book are also described.